Pendapat Ahli Kriminologi Tentang Pelaksanaan Sistem Peradilan Pidana Anak Dalam Prespektif Hukum Pidana Islam - Rosita Nur Alif Darma Santi; Salwa Salsabilla Putri; Siti Aisyah; Tutut Dwi Setyorini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In Indonesia, children who commit criminal acts often occur. Even though they have a special designation, namely children, they are still legally processed, in accordance with current legal developments in Indonesia. Therefore, Indonesia has a special court that regulates crimes committed by children, namely Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study uses normative and empirical juridical research methods. Normative juridical is carried out by analyzing the sources of primary legal materials, namely laws, journals, theses, and books contained in the literature. Empirical juridical is carried out by collecting data through interviews with criminologists who have a deep understanding of the juvenile justice system and Islamic criminal law. The data obtained from the interviews will be analyzed qualitatively to identify the views of criminologists regarding the implementation of the juvenile justice system in the context of Islamic criminal law. This study aims to analyze the opinions of criminologists regarding the implementation of the juvenile justice system in the perspective of Islamic criminal law.